2000
DOI: 10.1034/j.1399-0012.2000.0140s3015.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute humoral rejection of kidney allografts in patients with a positive flow cytometry crossmatch (FCXM)

Abstract: The patients with a positive flow cytometry crossmatch (FCXM) are categorized as a high-risk group causing hyperacute or accelerated acute rejection after kidney transplantation. According to the successful results of ABO-incompatible renal transplantation, we have performed the living related transplant operations in the recipients with positive FCXM for donor T cells, but having a negative complement-dependent lymphocytotoxic reaction test. We have followed the clinical course of 4 FCXM-positive patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
13
1
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10] However, in these reports the immunosuppressive agents and preoperative treatment are different from the present situation. Good outcomes using rituximab, plasma exchange (PEX), and intravenous immunoglobulin (IVIG) have been reported in immunologically high-risk patients.…”
Section: Introductioncontrasting
confidence: 44%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] However, in these reports the immunosuppressive agents and preoperative treatment are different from the present situation. Good outcomes using rituximab, plasma exchange (PEX), and intravenous immunoglobulin (IVIG) have been reported in immunologically high-risk patients.…”
Section: Introductioncontrasting
confidence: 44%
“…Such patients often are positive for FCXM, which has higher sensitivity than complementdependent cytotoxicity. Many studies have reported a poor prognosis in FCXM T+B+ patients, [3][4][5][6][7][8][9][10] and transplant was considered contraindicated in these patients in some treatment centers, depriving these patients from receiving a transplant. In many of these reports, there was no discussion of desensitization, immunosuppressive agents used, or perioperative treatment, which may have differed from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of kidney graft recipients become susceptible to AMR as a consequence of presensitization to donor antigens or sensitization following transplantation, particularly those who exhibit markedly elevated levels of circulating donor-reactive (HLA-specific) antibody (1,2). Current strategies are focused on reducing levels of pre-existing antibodies or attenuating primary humoral immune responses, including in vivo immunoadsorption, plasmapheresis and intravenous immunoglobulin, anti-CD20 treatment and splenectomy (5)(6)(7)(8)(9)(10)(11). Current strategies are focused on reducing levels of pre-existing antibodies or attenuating primary humoral immune responses, including in vivo immunoadsorption, plasmapheresis and intravenous immunoglobulin, anti-CD20 treatment and splenectomy (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This decline in the incidence of rejection is also notable for advances in the identification and treatment of “steroid‐resistant” rejection episodes, the majority of which are now known to be antibody mediated (4–7). These advances are not solely due to more effective immunosuppression medications, as advances in transplant crossmatching (8–13), identification of donor‐specific alloantibodies (14), and immunohistochemical identification of antibody‐mediated rejection by C4d staining (4,6,7,15–19) have all played a role. Still, it is not an exaggeration to say that acute cellular and antibody‐mediated rejection have become, for the majority of patients, treatable and reversible conditions.…”
mentioning
confidence: 99%